(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Understanding and analyzing the role of parental disciplining practices in these areas is essential for several reasons. parental disciplining practices significantly influence a child’s educational journey. The way parents enforce rules, provide guidance, and handle discipline shapes a child’s attitude towards learning, their work ethic, and their academic achievements. A well-structured and supportive approach to discipline can enhance a child’s academic performance, while overly harsh or inconsistent methods may hinder their progress. Maintaining discipline among children is essential for their personal growth and social development. Discipline helps children learn self-control, responsibility, and respect for rules and boundaries.